Microplastic pollution in the intertidal and subtidal sediments of Vava'u, Tonga. (January 2023) - Markic, Ana; Bridson, James H.; Morton, Peta; Hersey, Lucy; Budiša, Andrea; Maes, Thomas; Bowen, Melissa
Abstract: Plastic pollution research on a global scale intensified considerably in the current decade; however, research efforts in the South Pacific are still lagging. Here, we report on microplastic contamination of intertidal and subtidal sediments in the Vava'u archipelago, Tonga. While providing the first baseline data of its type in Tonga, the study also advances methods and adjusts them for low-budget research. The methods were based on density separation of microplastics from the sediment using CaCl2, a high-density salt which due to its high solubility, low cost and availability. Once separated, microplastics were quantified by microscopic analysis and polymers characterized via FTIR spectroscopy. Microplastics in intertidal and subtidal sediments were found in concentrations of 23.5 ± 1.9 and 15.0 ± 1.9 particles L −1 of sediment, respectively. The dominant type of microplastics in both intertidal (85 %) and subtidal sediments (62 %) were fibres. Highlights: This study is the first microplastics research of the intertidal and subtidal sediments of Vava'u, Tonga. Density separation of microplastics from the sediments was done using a CaCl2 solution. The dominant type of microplastics in both intertidal (85 %) and subtidal sediments (62 %) was fibres. Intertidal microplastics were mainly larger than 1 mm, while the subtidal microplastics were generally smaller than 1 mm.